2019
DOI: 10.1080/07434618.2018.1558283
|View full text |Cite
|
Sign up to set email alerts
|

Designing effective AAC displays for individuals with developmental or acquired disabilities: State of the science and future research directions

Abstract: This paper reviews research on the impact of AAC display variables on visual attention and performance of children with developmental disabilities and adults with acquired conditions, and considers implications for designing effective visual scene displays (VSDs) or grids. When using VSDs with children with developmental disabilities or adults with acquired conditions, research supports the use of personalized photo VSDs that include familiar people engaged in meaningful activities, with navigation bars with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Photos were still the most preferred aided communication mode unless a child vignette featured both predicted progress and motivation to communicate via AAC. This preference for photos possibly indicates that photos remain a good starting point for a child who is not engaged, regardless of prognosis, and may reflect recommendations that recognise the need to reduce the learning demands of AAC systems for some children 12 60…”
Section: Discussionmentioning
confidence: 99%
“…Photos were still the most preferred aided communication mode unless a child vignette featured both predicted progress and motivation to communicate via AAC. This preference for photos possibly indicates that photos remain a good starting point for a child who is not engaged, regardless of prognosis, and may reflect recommendations that recognise the need to reduce the learning demands of AAC systems for some children 12 60…”
Section: Discussionmentioning
confidence: 99%
“…For children scenes that depict familiar action routines allow for ready participation in routines and the emphasis is on quick capture of scenes to be used "in the moment" or "just in time (Wilkinson, et al, 2012). For adults, scenes can help support communication with familiar and unfamiliar partners based on significant life events and through photos with strong indicators of context and people involved (Light et al, 2019).…”
Section: Abstract/summarymentioning
confidence: 99%
“…3. 59,60 The main VSDs contained two children engaged in a shared activity. Results demonstrated that individuals with DS and other developmental disabilities spent greater than 75% of their viewing time on the meaningful elements within the VSD (i.e., children and shared activity), and less than 25% of their viewing time on the background.…”
Section: Early Sensory-perceptual Milestones and System Design Suggesmentioning
confidence: 99%
“…Participants spent the majority of their viewing time on the main VSD (M ¼ 61-67%) and less time on the navigation bar (M ¼ 30-33%). 59,60 Another consideration related to sensory perception is the use of motion. Motion may be used to draw attention to a stimulus or elicit the associated functional or behavioral characteristics of the stimulus (e.g., a shovel is used to dig).…”
Section: Early Sensory-perceptual Milestones and System Design Suggesmentioning
confidence: 99%